Taxonomic characterization and identification of Saccharomyces cerevisiae D8 for brandy production from pineapple - Le Thuong, Hoang Thi; Hao, Nguyen Quang; Thuy, Tran Thi (Academia Journal of Biology, 2018)
Eight yeast strains (denoted as D1 to D8) were isolated from samples of natural fermented pineapple. Strain D8 showed highest alcoholic production at low pH and special aroma of pineapple has been chosen for further study. Taxonomic characterization of strain D8 using morphological, biochemical and molecular biological studies confirmed that strain D8  belong to Saccharomycetaceae family, Saccharomycetales order and Saccharomyces cerevisiae species. Therefore, we named this strain as Saccharomyces cerevisiae D8 for further study on Brandy production from pineapple. Citation: Hoang Thi Le Thuong, Nguyen Quang Hao, Tran Thi Thuy, 2017. Taxonomic characterization and identification of Saccharomyces cerevisiae D8 for brandy production from pineapple. Tap chi Sinh hoc, 39(4): 474- 482. DOI: 10.15625/0866-7160/v39n4.10864.*Corresponding author: thuy_tt@hnue.edu.vn Received 5 December 2016, accepted 12 August 2017